Electroacupuncture Promoted Nerve Repair After Peripheral Nerve Injury by Regulating miR-1b and Its Target Brain-Derived Neurotrophic Factor - Liu, Yu-Pu; Luo, Zhi-rong; Wang, Chang; Cai, Hao; Zhao, Tian-tian; Li, Han; Shao, Shui-jin; Guo, Hai-dong (Frontiers in Neuroscience, 2020)
Growing evidence indicates that electroacupuncture (EA) has a definite effect on the treatment of peripheral nerve injury (PNI), but its mechanism is not completely clear. miRNAs are involved in the regulation of a variety of biological processes, and EA may enhance PNI repair by regulating miRNAs. In this study, the rat sciatic nerve injury model was treated with EA for 4 weeks. Acupoints Huantiao (GB30) and Zusanli (ST36) were stimulated by EA 20 minutes once a day, 6 days a week for 4 weeks. We found that EA treatment down-regulated the expression of miR-1b in the local injured nerve. In vitro experiments showed that overexpression of miR-1b inhibited the expression of brain derived neurotrophic factor (BDNF) in rat Schwann cells (SCs) line while BDNF knockdown inhibited the proliferation, migration and promoted apoptosis of SCs. Subsequently, the rat model of sciatic nerve injury was treated by EA treatment and injection of agomir-1b or antagomir-1b. The nerve conduction velocity ratio (NCV), sciatic functional index (SFI) and S100 immunofluorescence staining were examined and showed that compared with the model group, NCV, SFI, proliferation of SC and expression of BDNF in the injured nerves of rats treated with EA or EA + anti-miR-1b were elevated, while EA+miR-1b were reduced, indicating that EA promoted sciatic nerve function recovery and SCs proliferation through down-regulating miR-1b. To summarize, EA may promote the proliferation, migration of SC and nerve repair after PNI by regulating miR-1b which targets BDNF.